Landscape variability of riparian buffers and its impact on soil and water chemistry of an urbanized watershed. (April 2022) - Jaja, Ngowari; Mbila, Monday; Codling, Eton; Tsegaye, Teferi; Odutola, Jamiu
Highlights: Riparian zone processes affect soil chemistry and water quality of watersheds. There were clear pedogeomorphic variability at Aldridge Creek Watershed in Alabama. Trace metal distribution and re-distribution in the watershed has anthropogenic linkages. Riparian zones of each site influenced the concentration of the trace metal measured. Abstract: Water and sediment transport and redistribution around drainage ways are major riparian zone processes that affect soil chemistry and water quality of watersheds. This is more so for urbanized watersheds that generate more runoff and sediments which end up in the drainage ways. This study was done to evaluate the pedogeomorphic variability of the Aldridge Creek Watershed in Alabama, and to assess its impact on the water quality and soil properties of the watershed. Sampling locations along the creek were subdivided into five stream sites and geo-referenced. Soil samples from the riparian buffers and water samples from the creek were collected from upstream, midstream, and downstream sites of the watershed and analyzed for trace metal concentration and distribution. The trace metal concentration in soils of the riparian buffers varied from 20 to 34 µg g −1 for lead (Pb), 50–85 µg g −1 for zinc (Zn), 6–17 µg g −1 for copper (Cu), 11–18 µg g −1 for nickel (Ni) and 5–21 µg g −1 for arsenic (As). At all sites, Pb, Zn, Ni, Cu and As concentrations in the riparian zone locations were 7–67% higher than the upper slopes indicating that the riparian zone is a potential source or sink of trace metals along the flow pathways between the upper slope soils and the stream. While there were significant differences in the distribution of trace metals in soils between the upslope and riparian zone locations at the upstream, midstream, and downstream sites, there was no significant difference in the stream water trace metals concentration between the sites of the watershed.